PERIOPERATIVE WARMING INTERVENTIONS TO PREVENT HYPOTHERMIA IN ADULT DIGESTIVE SURGERY: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS - Azzahra Sida Puspaningrum (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Perioperative hypothermia remains a clinical challenge that frequently occurs in patients undergoing digestive system surgery. However, this incident is still considered a minor complication. However, if this condition is not managed properly, it can lead to various complications, such as cardiac arrhythmia, ischemia, risk of infection, decreased wound healing, and various other complications. Preventive management of perioperative hypothermia through environmental modifications, providing unheated or heated blankets, warm infusion therapy, and the use of technology can reduce the incidence of hypothermia, shivering, accelerate the recovery process, minimize infection, and improve patient comfort. Objective: To evaluate the effectiveness of hypothermia prevention management in patients undergoing digestive system surgery in the perioperative phase. Methods: A systematic review was conducted following the PRISMA guidelines by searching for various relevant articles from 5 databases: Scopus, PubMed, Proquest, Web of Science, and Sage. Inclusion criteria for articles were published within the last 5 years (2021-2026), using a Randomized Controlled Trial (RCT) design, using English, and discussing interventions to prevent hypothermia in cases of digestive system surgery in the perioperative phase. Results: Twelve articles out of 535 identified were deemed eligible and met the inclusion criteria . Rewarming/peri-induction forced-air warming and composite or multimodal warming strategy were the most significant interventions in reducing the incidence of perioperative hypothermia compared to other interventions such as room heaters, heated blankets, non-heated blankets, and warm infusion therapy. Conclusion: Hypothermia prevention management is effective in reducing the incidence of perioperative hypothermia in the perioperative phase.